A Self-Sustainable and Micro-Second Time Synchronized Multi-Node Wireless System for Aerodynamic Monitoring on Wind Turbines - Tommaso Polonelli; Amirhossein Moallemi; Weikang Kong; Hanna Muller; Julien Deparday; Michele Magno; Luca Benini (IEEE Access, 2023)
Wind energy generation plays a vital role in transitioning from fossil fuel-based energy sources and in alleviating the impacts of global warming. However, global wind energy coverage still needs to rise, while requiring a significant step up in conversion efficiency: monitoring wind flow and operational parameters of wind turbines is an essential prerequisite for coverage and conversion efficiency optimization. This paper presents a low-power, self-sustainable, and time-synchronised system for aerodynamic and acoustic measurements on operating wind turbines. It includes 40 high-accuracy barometers, 10 microphones, 5 differential pressure sensors, and implements a coarse time synchronisation on top of a Bluetooth Low Energy 5.1 protocol tuned for long-range communications. Moreover, we field-assessed the node capability to collect precise and accurate aerodynamic data with a multi-node setup. Outdoor experimental tests revealed that the system can acquire heterogeneous data with a time synchronisation error below $\mathrm {100~ μ \text {s} }$ and sustain a data rate of 600 kbps over 400 m with up to 5 sensor nodes, enough to fully instrument a wind turbine. The proposed method does not add any traffic overhead on the Bluetooth Low Energy 5.1 protocol, fully relying only on connection events and withstands transmission discontinuity often present in long range wireless communications.